First-In-Human Study on Pharmacokinetics, Safety, and Tolerability of Single and Multiple Escalating Doses of Hepenofovir, a Novel Hepatic Targeting Prodrug of Tenofovir in Healthy Chinese Subjects - Zhang, Hong; Gao, Lei; Lou, Jinfeng; Wu, Min; Chen, Hong; Yang, Lizhi; Liu, Jingrui; Zhu, Xiaoxue; Li, Xiaojiao; Li, Cuiyun; Wang, Meng; Liu, Chengjiao; et al. (Frontiers in Pharmacology, 2022)
Objective: Hepenofovir, a novel hepatic targeting prodrug of tenofovir, has been developed for the treatment of chronic hepatitis B (CHB). This is a first-in-human study to evaluate the pharmacokinetics (PK) and tolerability of single and multiple escalating doses of hepenofovir in healthy Chinese subjects. Methods: This phase Ia study included two parts: a double-blinded, randomized, placebo-controlled single-ascending-dose (SAD) (25-200 mg) study under fasted conditions comprising a food-effect investigation (200 mg) and a multiple-ascending-dose (MAD) (25 mg) study under fasted conditions. Results: Hepenofovir was well tolerated in healthy Chinese subjects. There was no significant difference in adverse reaction rates between hepenofovir and placebo groups. Hepenofovir was rapidly absorbed and metabolized into tenofovir after dosing. In healthy participants, the median Tmax of hepenofovir and tenofovir was 0.33–0.50 h and 0.62-0.75 h, respectively, and their mean half-life was 2.5-12.3 h and 49.7-53.8 h, respectively. Systemic exposure to tenofovir increased in proportion to the dose. The mean accumulation indexes of hepenofovir and tenofovir were 1.1 vs 1.8. Moreover, food could reduce the Cmax of both hepenofovir and tenofovir, but did not affect their area under the curve (AUC). Conclusions: Hepenofovir has shown a favorable safety and PK profile, which support the further evaluation of its safety and efficacy in CHB patients.